Dynamic Communications Between GABAA Switch, Local Connectivity, and Synapses During Cortical Development: A Computational Study - Khalil, Radwa; Karim, Ahmed A.; Khedr, Eman; Moftah, Marie; Moustafa, Ahmed A. (Frontiers in Cellular Neuroscience, 2018)
Several factors regulate cortical development, such as changes in local connectivity and the influences of dynamical synapses. In this study, we simulated various factors affecting the regulation of neural network activity during cortical development. Previous studies have shown that during early cortical development, the reversal potential of GABAA shifts from depolarizing to hyperpolarizing. Here we provide the first integrative computational model to simulate the combined effects of these factors in a unified framework, which builds on our prior work (Khalil et al., 2017a, 2017b). Unlike our prior computational models, in the current study, we extend our model to monitor firing activity in response to the excitatory action of GABAA. Specifically, we designed a Spiking Neural Network (SNN) model, in which we incorporated parameters for lateral connectivity (distance between adjacent neurons) and the nearby local connectivity (complex connections involving those between neuronal groups). We simulated different network scenarios (for immature and mature conditions) based on these crucial parameters. Then, we implemented two classes of dynamical synapses (i.e., Short-term synaptic plasticity (STP)): Short-term depression (STD) and Short-term facilitation (STF). Each class has two different forms based on the parametric value of its synaptic time constant, either for depressing or facilitating synapses. Lastly, we compared the responses of firing rate activity before and after simulating dynamical synapses in both kinds of networks. Based on simulation results, we found that the modulation effect of dynamical synapses for evaluating and shaping the firing activity of the neural network is strongly dependent on the physiological state of GABAA. Moreover, the STP mechanism acts differently in every network scenario, mirroring the crucial modulating roles of these critical parameters during cortical development. Clinical implications for pathological alterations of GABAerig signaling in neurological and psychiatric disorders are discussed.